Effect of Particle Magnetic Moment Distribution on Magnetization of Antiferromagnetic Nanoparticle Systems - Rani, Chandni (My University, 2018)
In this thesis, synthesis, structural and magnetic characterization of two lines ferrihydrite, six lines ferrihydrite and nickel oxide-two lines ferrihydrite nanocomposite are presented. Both types of ferrihydrite decompose to hematite on heating in air. The magnetization data in superparamagnetic region are analyzed to study the role of particle magnetic moment distribution on the magnetization process. The particle magnetic moment distribution present in each sample is also estimated. This work also provides an easy and convenient method to estimate particle concentration in a nanocomposite sample.
Doctor of Philosophy -SPMS
Keywords: Nanoparticles; Magnetization